Lifecycle Impact Assessment of an Engineering Project Management Process – A SLCA Approach - Hrakam, Niguharara; Umaimahs Fakataah (IPHO-Journal of Advance Research in Science And Engineering, 2024)
Engineering projects are designed to solve societal problems, foster community development, and enhance quality of life. However, these projects often have unintended consequences that affect human life and ecosystems. The management process of these projects significantly influences their social, environmental, and economic impacts. This paper presents a framework for evaluating the lifecycle impacts of engineering project management processes on various stakeholders, including workers, clients, communities, and society at large. The model adopts the UNEP/SETAC guidelines for Social Lifecycle Impact Assessment (SLCA). By identifying potential impacts during the lifecycle stages, project managers can reinforce positive outcomes and mitigate negative effects. Incorporating SLCA in project management is expected to improve overall project value, particularly from a social sustainability perspective